Value for money in public procurement: Experience from Zimbabwe’s rural district councils - David Chikwere; Lovemore Chikazhe; Marian Tukuta (Cogent Social Sciences, 2023)
AbstractThe method by which government and public institutions make acquisitions lays the groundwork for development of rural district councils by enabling critical investments in terms of physical infrastructure and institutional capacity building. The purpose of this study was to establish the relationship between procurement objectives, procurement process, procurement management, and value for money on Zimbabwe’s Rural District Councils (RDCs). The study was guided by the Practice Based View and the Supply Chain Practice Perspective. A structured, closed-ended, self-administered Google form questionnaire was used to collect responses from 30 out of 60 randomly chosen RDCs in Zimbabwe. 207 useful responses were obtained from 264 supervisory staff and procurement officials. The procurement process, procurement objectives, and procurement management were found to positively influence value for money. The results also indicate that procurement objectives positively influenced the procurement process, while the procurement process was found to have a positive effect on procurement management. This study provides fresh insights and validates existing knowledge on the procurement process, procurement objectives, procurement management, and value for money in the RDCs. As this study demonstrates how procurement practices have a direct impact on value for money, it advances our understanding of public procurement and value for money in developing countries like Zimbabwe. Moreover, the study findings support both the Practice Based View and the Supply Chain Practice Perspective in that the results show that procurement practices when effectively managed and aligned with the objectives of the organization, they contribute to achieving value for money in procurement. outcomes.